Study on the expression of interleukins in patients with twin-twin transfusion syndrome - Duy Anh, Nguyen; Thi Sim, Nguyen; Huyen Thuong, Phan; Thi Phuong Thao, Tran; Van Tong, Hoang; Duy Bac, Nguyen; Thi Lan Anh, Luong; Thi Thu Canh, Than (Vietnam Journal of Biotechnology, 2020)
Twin-twin transfusion syndrome (TTTS) is an unusual and serious condition that occurs in twin pregnancies when identical twins share a placenta but develop discordant amniotic fluid volumes. The TTTS has a high risk of fetal death and birth defects if left untreated. IL-1β, IL-6 and IL-8 have been shown to play an important role in preterm birth in twin pregnancies, which is one of the consequences of TTTS. This study quantified plasma levels of IL-1β, IL-6 and IL-8 in twin pregnant women with (n = 52) and without TTTS (n = 73) by ELISA and analyzed the association of interleukin expression levels with TTTS. The results showed that plasma concentrations of IL-1β and IL-8 were low and not significantly different between the first trimester and the second trimester of pregnancy, between the patients with and without TTTS or between patients with TTTS before and after treatment. IL-6 levels showed no significant difference between first trimester and second trimester of pregnancy or between patients with and without TTTS. Importantly, IL-6 levels were significantly elevated in TTTS patients after surgical treatment compared to those before surgical treatment. In conclusion, IL-6 may be considered as a potential marker for the prognosis of surgical treatment of TTTS.